Controlling the pandemic during the SARS-CoV-2 vaccination rollout - João Viana (Nature Portfolio, 2021)
Despite the consensus that mass vaccination against SARS-CoV-2 will ultimately end the pandemic, it is not clear when and which control measures can be relaxed during the rollout of vaccination programmes. Here, the authors investigate relaxation scenarios using an age-structured transmission model that has been fitted to data for Portugal.